DEVELOPMENT OF TOURISM POTENTIAL IN WATERSPORTS RECREATION, SANTIRAH RIVER, PANGANDARAN REGENCY, INDONESIA - Rahmafitria, Fitri; Wirakusuma, Reiza Miftah; Riswandi, Agus (PEOPLE: International Journal of Social Sciences, 2017)
River is one of a recreational resource potential of watersport in Indonesia. The growing trend of sports tourism in water-based recreation, making some rivers and rapids with unique morphology, being developed by the local community as a tourism destination. Furthermore, comprehensive planning and meticulous study, is the key to develop sustainable sports tourism. This study was conducted as a series of special interest travel planning process-based education that used the river with River Tubing Activity as an attraction. The sample was taken on Santirah River which is currently growing as one of a favorite attraction in West Java, Indonesia. The survey was conducted through observation of the physical condition of the river and the readiness of human resources management. As a result, Santirah river has high potential from the physical aspect, however the readiness still low on aspect of human resources to provide safe and convenient service. The role of governments and professional organizations in the field of sports recreation are essential in providing assistance to the managing authority in this river.